2004
DOI: 10.1111/j.1475-3995.2004.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of models and methods for strategic planning: Towards an holistic view of strategy

Abstract: Formulating manufacturing business strategy is often fragmented in as much as current tools address upstream and downstream vertical integration with product integration, or more recently, product and infrastructure integration. Rarely do tools address all of these dimensions in an holistic manner. The research described in this paper is that undertaken in the MAPSTRAT project: a scoping study with industrial partners, aiming to satisfy this business need. A comprehensive literature study is described which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Such an approach is needed as it includes an exhaustive coverage of the research topic in question by looking at that topic from various angles and into multiple components. A holistic approach looks at a research topic from both the resource and the activity perspectives (Philpott et al, 2004). And by integrating these angles, components and perspectives, the holistic approach provides a better understanding of the research topic and its accompanying variables (Hardi and Buti, 2012).…”
Section: Research On High Performance In Asiamentioning
confidence: 99%
“…Such an approach is needed as it includes an exhaustive coverage of the research topic in question by looking at that topic from various angles and into multiple components. A holistic approach looks at a research topic from both the resource and the activity perspectives (Philpott et al, 2004). And by integrating these angles, components and perspectives, the holistic approach provides a better understanding of the research topic and its accompanying variables (Hardi and Buti, 2012).…”
Section: Research On High Performance In Asiamentioning
confidence: 99%
“…Theorists are in full agreement, however, that from core competence view, strategists should analyse firms in terms of their competence, resources and activity so that they can more fully address decisions on the upstream and downstream vertical axis (Philpott, Hamblin, Baines, & Kay, 2004). In terms of TCE, it has also been shown that vertical integration is utilized when a company seeks to expand its activities, such as through the franchise system, in the presence of uncertainty regarding the success of the business.…”
Section: Operations Strategymentioning
confidence: 99%
“…Leading up to the research presented in this paper, our previous work has investigated the principles on which manufacturers should form their strategic positioning decision. This was based on survey‐ and case‐based research as reported in Baines and Kay (2002) and Philpott et al (2004). This earlier research revealed three key principles that leading manufacturers apply when making these decisions.…”
Section: Background and Previous Researchmentioning
confidence: 99%